Why Becoming Diocesan Priests? - Melania; Ujianto; Mulyanto Nugroho (Archives of Business Research, 2022)
This research aims to explore the motives that drive a person becoming a diocesan priest in the beginning, using qualitative methods with a phenomenological approach by conducting indepth interview to six diocesan priests who serve in the Diocese of Banjarmasin. Identified themes classified according to construct of the theory of planned behaviour (TPB): subjective norms. Results showed that closeness to parents, missionary dedication, and the exemplary of role models are the motives that drive a person in his childhood to become a diocesan priest. Propositions obtained through this research (i) the closer and more trusting family members are to the family, the stronger the influence of the family to form a person’s life motive / purpose; (ii) the stronger the urge to commit dedication and totality, the stronger the intention and belief of becoming a diocesan priest; (iii) The stronger the support of the environment and community, the stronger the formation of intentions in a person.